2012
DOI: 10.1063/1.4759352
|View full text |Cite
|
Sign up to set email alerts
|

Temperature dependence of magnetic anisotropy constant in iron chalcogenide Fe3Se4: Excellent agreement with theories

Abstract: Magnetic hysteresis loops were measured for ferrimagnetic iron chalcogenide Fe 3 Se 4 nanoparticles in the whole temperature range below the Curie temperature T C (315 K). The coercivity of the material is huge, reaching about 40 kOe at 10 K. The magnetic anisotropy constant K was determined from the magnetic hysteresis loop using the law of approach to saturation. The deduced anisotropy constant at 10 K is 5:22 Â 10 6 erg=cm 3 , which is over one order of magnitude larger than that of Fe 3 O 4 . We also demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 19 publications
4
36
0
Order By: Relevance
“…Although the analysis of the diffraction data may allow to assign a monoclinic structure of the inclusions, further analysis of our magnetization data are not entirely consistent since the monoclinic Fe 3 Se 4 is reported to be ferrimagnetic [40,44,45] with the magnetic transition temperature and hysteretic magnetization curve even above room temperature. Our magnetization measurements are hysteretic at low temperatures but do not indicate such a behavior for the SC sample at room temperature where only an S-shape is seen.…”
Section: 2791(17) Fe2mentioning
confidence: 67%
See 1 more Smart Citation
“…Although the analysis of the diffraction data may allow to assign a monoclinic structure of the inclusions, further analysis of our magnetization data are not entirely consistent since the monoclinic Fe 3 Se 4 is reported to be ferrimagnetic [40,44,45] with the magnetic transition temperature and hysteretic magnetization curve even above room temperature. Our magnetization measurements are hysteretic at low temperatures but do not indicate such a behavior for the SC sample at room temperature where only an S-shape is seen.…”
Section: 2791(17) Fe2mentioning
confidence: 67%
“…Our magnetization measurements are hysteretic at low temperatures but do not indicate such a behavior for the SC sample at room temperature where only an S-shape is seen. Moreover, the hysteretic magnetization curve of the SC sample has two-step character in contrast to a simple hysteresis found in Fe 7 Se 8 [44]. However, the magnetic properties of Fe 7 Se 8 are reported to be very sensitive to iron deficiency, causing vacancies ordered within the lattice.…”
Section: 2791(17) Fe2mentioning
confidence: 84%
“…As far as the magnetic property of such composite-nanostructure is concerned, the absence of a hysteresis loop in the field-dependent magnetization measurement illustrated the superparamagnetic nature of FeSe 2 /Bi 2 Se 3 -PEG [17] (Supporting Figure S11). T2-weighted MR images of a series of concentrations of FeSe 2 /Bi 2 Se 3 -PEG solutions acquired by a 3T MR scanner revealed the concentration-dependent darkening effect (Figure 3C).…”
Section: Resultsmentioning
confidence: 99%
“…It is important to stress that the temperature dependence of the anisotropy has been also considered in attention to experimental works reported [14][15][16] as well as the cubic anisotropy distortion on the surface and grain boundaries, where an important local structural disorder is expected. Studies obtained by ab-initio calculations and experimental processes have shown that the electronic configuration of the atoms belonging to these regions is significantly different respect to the extended and homogeneous crystalline medium in the core of the grains [17][18][19][20] .…”
Section: Model Descriptionmentioning
confidence: 99%